InVitro Models of Intestine Innate Immunity. Issue 3 (March 2021) - Roh, Terrence T.; Chen, Ying; Rudolph, Sara; Gee, Michelle; Kaplan, David L.
Abstract : Animal models have delivered critical insights into mechanisms underlying the intestinal innate immune system; however, inherent differences exist between human and animal systems. To further understand the intestine innate immune system, there is a growing need for in vitro tissue model systems using human cells. A critical feature of in vitro cell and tissue models is the subepithelial environment, which contains additional cell types and includes 2D, microfluidic, organoid, and 3D tissue models. Where mouse models for the study of intestinal innate immune systems fall short, developments from in vitro models continue to grow in importance to aid efforts to understand this system in the context of disease and potential treatments. Highlights: Studies using cocultures with multiple human cell types and microbial populations show interactions (cell signaling) between cell types, enhancing model fidelity to native human intestine tissue. Nontransformed human intestinal organoids are replacing cell lines in in vitro model platforms, improving the physiological relevance of models, including patient-specific characteristics. 3D tissue culture systems provide attachment sites for cell migration and stromal-like contents under an epithelial layer to better mimic the complex structural organization of intestinal tissue. Fluid flow across the intestinal epithelium contributes to improved epithelial barrier function with impact on in vitro microbial interactions with the epithelium. 3D tissue models support inflammation components (e.g., macrophages) and innervation, as key components of a human intestinal model to study diseases.